Imaging Measurement Methods for Flow Analysis Results of the DFG Priority Programme 1147 "Imaging Measurement Methods for Flow Analysis" 2003-2009 - Nitsche, Wolfgang; Dobriloff, Christoph (Notes on Numerical Fluid Mechanics and Multidisciplinary Design, 2009)
This volume contains the results of the priority programme Imaging Measurement Methods for Flow Analysis conducted in 2003-2009. This research programme was based on the fact, that experimental flow analysis has always played an important role in addition to theory and numerics. At the time, however, comparisons with numerical tools made it clear, that there are only few experimental procedures which can keep up with these increasingly powerful tools in respect to their informative value. The priority programme was to close this development gap by focusing on the investigation on efficient measurement methods to analyse complex flow fields and advancing these techniques to a widely renowned key technology. This book gives a state-of-the-art overview of current developments in the fields of image based flow measurements and analysis. The contributions to this book were presented at the concluding conference of the programme held May 14 - 15, 2009, at the Technische Universität Berlin, Germany. The priority programme was funded by the DFG (German Research Foundation).